Prevalence of Cholelithiasis and Associated Factors of Gallstone Formation after Laparoscopic Sleeve Gastrectomy in the Gastroenterology and Hepatology Teaching Hospital-Baghdad - Mohammed, Abdulrahman M.; Mohammed, Abdulnaser M.; Hassan, Tuka Y. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Bariatric surgery (BS) is the most effective method for long-term weight loss. Rapid weight reduction after BS may contribute to the formation of gallstones. Objectives: To assess the rate, and to identify the associated factors, of gallstone formation after laparoscopic sleeve gastrectomy. Methods: This was a cross-sectional study among 128 patients with morbid obesity, who were treated with laparoscopic sleeve gastrectomy and followed up at two weeks, one month, six months, and one year after surgery between October 2018 and July 2020, at the Gastroenterology and Hepatology Teaching Hospital in Baghdad and the Dowaly Private Hospital. Data was collected using a structured questionnaire. Results: The mean age of patients was 36.5±5.21 (17–54) for females and 41.6 ±3.04 (24–58) for males. Gallstone formation happened in 49 cases (38.3%). Of all males, four (36.4%) developed gallstones after (LSG), compared to 45 (38.5%) females. Sixty (46.9%) patients had a Body Mass Index (BMI) ≥40 kg/m2, of whom 29 (48.3%) developed gallstones after LSG (p = 0.031). The p-values for weight loss regarding timing and degree of loss show a significant relationship with gallstone formation after LSG (p < 0.05). Comorbid conditions were not significantly associated with the incidence of gallstone formation after LSG (p > 0.05). Conclusions: More than a third of the cases developed gallstones after Laparoscopic Sleeve Gastrectomy. This was associated with Gross obesity prior to surgery (BMI ≥ 40 kg/m²), losing ≥25% of the original weight, and rapid weight loss during the first six months after LSG.